TRACING THE HISTORICAL TRACES OF THE ENTRY OF ISLAM IN MAHALA VILLAGE, TINADA DISTRICT, PAKPAK BHARAT REGENCY: MENELUSURI JEJAK SEJARAH MASUKNYA ISLAM DI DESA MAHALA, KECAMATAN TINADA KABUPATEN PAKPAK BHARAT - Febiola Br Berutu; Laila Rohani (SOSIOEDUKASI, 2025)
This article examines the process of the entry of Islam into Mahala Village, Tina District, Pakpak Bharat Regency, an area where the majority of the population still adheres to the school of faith and is located in the interior of North Sumatra. This historical search was carried out to fill the void of local historical literature regarding the spread of Islam in the Pakpak area which has received less attention in academic studies. The main focus of this research is to identify the path of entry of Islam, what are the evidence of Islamic historical heritage and analyze the influence of Islam on the people of Mahala village, especially in social and cultural aspects. This research uses a qualitative method with a historical approach. Data was collected through in-depth interviews with community leaders, religious leaders, as well as direct observation of historical sites such as old tombs in Lae Meang Hamlet. In addition, secondary sources of documentation are used in the form of articles, archives, and oral historical records. The results of the study show that Islam began to be known in Mahala Village around the 1920s, as evidenced by the existence of the tombs of Islamic propagators with the year of death written between 1923-1927. The process of spreading Islam took place peacefully through trade routes and social interactions, especially by immigrants from Aceh and Barus. Important figures in this process include Teuku Panjang Rambut and Abdurrahim Berutu. Although the Muslim community in Mahala remains a minority, their existence is harmoniously accepted by the local community. The conclusion of this article shows that the process of Islamization in Mahala Village took place culturally and peacefully, not through confrontation. This shows the importance of a social and locality approach in understanding the dynamics of the spread of religion in multicultural areas such as Pakpak Bharat.